Quantification of NETs‐associated markers by flow cytometry and serum assays in patients with thrombosis and sepsis. (9th March 2018) - Lee, K. H.; Cavanaugh, L.; Leung, H.; Yan, F.; Ahmadi, Z.; Chong, B. H.; Passam, F.
Abstract: Introduction: Neutrophil extracellular traps (NETs) are networks of extracellular fibres produced from neutrophil DNA with a pathogenic role in infection, thrombosis and other conditions. Reliable assays for measuring NETs are desirable as novel treatments targeting NETs are being explored for the treatment of these conditions. We compare a whole blood flow cytometry method with serum assays to measure NETs‐associated markers in patients with sepsis and thrombosis. Methods: Patients with deep venous thrombosis (n = 25), sepsis (n = 21) and healthy controls (n = 23) were included in the study. Neutrophil surface NETs markers were determined by flow cytometry on whole blood samples by gating of neutrophils stained for surface citrullinated histone (H3cit) and myeloperoxidase (MPO). Serum double‐stranded (ds) DNA, MPO, myeloid‐related protein, nucleosomes, DNAse, elastase, human high‐mobility group box 1 and MPO‐DNA complexes were quantified as circulating markers of NETs. Results: Neutrophil NETs markers by flow cytometry and serum NETs markers were significantly higher in patients with thrombosis and sepsis compared with healthy controls. Neutrophil NETs markers significantly correlated with the serum marker dsDNA. Conclusion: Flow cytometry detection of neutrophil NETs markers is feasible in whole blood and correlates with serum markers of NETs. We propose the flow cytometry detection of MPO/H3cit positive neutrophils and serum dsDNA as simple methods to quantify cellular and extracellular NET markers in patients with thrombosis and sepsis.